MENILAI KONDISI KESEHATAN KEUANGAN PT BANK PERMATA, TBK DIMASA PANDEMI COVID-19 - Stenly Jacobus Ferdinandus (Soso-Q : Jurnal Manajemen, 2020)
This study aims to determine the financial health condition of banks at PT Bank Permata, TBk during the COVID-19 pandemic by using the CAMEL method even though Bank Indonesia has perfected the health assessment method from CAMELS to RGEC in accordance with SE BI number 13/24 / DPNP dated 25 October 2011 concerning The Rating of Commercial Bank Soundness is an implementation guideline for Bank Indonesia Regulation No.13 / 1 / PBI / 2011. The reason the researcher does not use RGEC is because the Capital assessment in CAMELS uses credit and market risk, does not see the operational risk used in RGEC. Then. The ASSET assessment in CAMELS uses the NPL, RORA, PPAP ratio indicators while in the RGEC assessment there is no asset assessment.The population in this study is the financial statements of PT Bank Permata, Tbk. With a sample of 4 financial reports for the period of the fourth quarter of 2019 to the third quarter of 2020 based on the purposive sampling method. The analysis technique used is descriptive quantitative analysis. The data source of this research uses secondary data sources obtained from the Indonesia Stock Exchange (IDX).The results of the study found that the CAMEL value at the time of the COVID-19 pandemic in 2019, the fourth quarter showed that the bank's financial health condition was NOT HEALTHY, in 2020 the first quarter showed that the financial health condition of the bank was NOT HEALTHY, in 2020 the second quarter showed the financial health condition of the bank in the condition is NOT HEALTHY and in 2020 the third quarter shows that the financial health condition of the bank is not HEALTHY.Kata Kunci: Bank Health Condition, CAMEL